Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Diatom (Skeletonema costatum) Skala Laboratorium di BPBAP Ujung Batee - Mivta Hujannah (Publikasi Indonesia, 2023)
Skeletonema costatum was a type of natural feed that has an important role in the hatcery of fish, shrimp, shellfish and crab. Skeletonema costatum is able to adapt to various salinities so it is able to live in the sea, beaches and river estuaries. This study aims to determine the factors that influence the growth of Skeletonema costatum diatoms cultured using different doses of vitamin mix at laboratory scale. This research was conducted at the Brackish Water Aquaculture Fisheries Center (BPBAP) Ujung Batee. This study each used 3 treatments and 9 repetitions with 3 doses of vitamin mix 0,5 ml, 1 ml and 1,5 ml. primary data was collected, was collection was carried out using experimental, primary data consisted of the process of culturing Skeletonema costatum, wet sterelization, dry sterelization, preparation of containers and observation of Skeletonema costatum samples using a microscope. From the density research chart it shows that in treatment 1 doses of 0,5 ml has the highest value of 1,243,056 and lowes value 651,111 on the third day, in treatment 2 doses of 1 ml has the highest value of 1,343,056 and lowes value 996,429 on the third day and treatment of 3 doses of 1,5 ml has the highest value of 1,577,813 and lowes value 1,051,813 based on the results of the density chart of 3 treatments and 9 repetitions of the vitamin mix, the highest density value was found in the 3 treatment doses of 1,5 ml with a value of 1,577,813 and lowes value 1,051,813..